Customer Experience and Customer Engagement as Predictors of Customer Loyalty at Local Coffee Shops - Akhmad Irwansyah Siregar (Greenation International Journal of Tourism and Management, 2026)
The local coffee shop industry is experiencing rapid growth, which has led to increased competition in retaining customer loyalty. Under these conditions, the ability to create positive customer experiences and foster customer engagement has become a critical factor in strengthening long-term relationships with customers. However, most previous studies have examined customer experience or customer engagement separately, while research integrating both variables as direct predictors of customer loyalty in the context of local coffee shops remains relatively limited. This study aims to analyze the influence of customer experience and customer engagement on customer loyalty at local coffee shops. This study employs a quantitative approach using a survey method involving 106 consumers of local coffee shops in Jambi City, selected through purposive sampling. Data analysis was conducted using multiple linear regression with the aid of SPSS 25.0. The results indicate that customer experience and customer engagement have a positive and significant effect on customer loyalty, both partially and simultaneously. The novelty of this study lies in the integration of the perspectives of customer experience and customer engagement as factors shaping loyalty in the context of local coffee shops, particularly in regions that have not been extensively studied.